A Lipid-Nanosphere-Small MyoD Activating RNA-Bladder Acellular Matrix Graft Scaffold [NP(saMyoD)/BAMG] Facilitates Rat Injured Bladder Muscle Repair and Regeneration [NP(saMyoD)/BAMG] - Jin, Chongrui; Cao, Nailong; Ni, Jianshu; Zhao, Weixin; Gu, Baojun; Zhu, Weidong (Frontiers in Pharmacology, 2020)
Background: Bladder tissue engineering is an excellent alternative to conventional gastrointestinal bladder enlargement in the treatment of various acquired and congenital bladder abnormalities. We constructed a nanosphere-small MyoD activating RNA-bladder acellular matrix graft scaffold (NP (saMyoD)/BAMG) inoculated with adipose-derived stem cells (ADSC) to explore its effect on smooth muscle regeneration and bladder repair function in a rat augmentation model. Methods: We performed many biotechniques, such as Reverse transcriptase-polymerase chain reaction (RT-PCR), Western blot, MTT assay, HE staining and immunohistochemical in our study. Lipid nanospheres were transfected into rat ADSCs after encapsulate saRNA-MyoD as an introduction vector. Lipid nanospheres encapsulated with saRNA-MyoD were transfected into rat ADSCs. The functional transfected rat ADSCs were called ADSC-NP(saMyoD). Then, Rat models were divided into four groups: sham group, ADSC-BAMG group, ADSCNP(saMyoD)/BAMG group and ADSC-NP(saMyoD)/SF(VEGF)/BAMG group. Finally, we compared the bladder function of different models by detecting the bladder histology, bladder capacity, smooth muscle function in each team. Results: RT-PCR and Western blot results showed that ADSCs transfected with NP(saMyoD) could induce high expression of α-SMA, SM22a and Desmin. At the same time, MTT analysis showed that NP(saMyoD) did not affect the activity of ADSC cells, suggesting little toxicity. HE staining and immunohistochemistry indicated that the rat bladder repair effect (smooth muscle function, bladder capacities) was better in the ADSC-NP(saMyoD)/BAMG group, ADSC-NP(saMyoD)/SF(VEGF)/BAMG group than in the control group. Conclusions: Taken together, our results demonstrate that the NP(saMyoD)/ SF(VEGF)/BAMG scaffold seeded with ADSCs could promote bladder morphological regeneration and improved bladder urinary function. This strategy of ADSC-NP(saMyoD)/SF(VEGF)/BAMG maybe has a potential to repair bladder defects in the future.